2011
DOI: 10.1021/ja2021747
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in the Rechargeable Lithium–O2 Battery with Alkyl Carbonate Electrolytes

Abstract: The nonaqueous rechargeable lithium-O(2) battery containing an alkyl carbonate electrolyte discharges by formation of C(3)H(6)(OCO(2)Li)(2), Li(2)CO(3), HCO(2)Li, CH(3)CO(2)Li, CO(2), and H(2)O at the cathode, due to electrolyte decomposition. Charging involves oxidation of C(3)H(6)(OCO(2)Li)(2), Li(2)CO(3), HCO(2)Li, CH(3)CO(2)Li accompanied by CO(2) and H(2)O evolution. Mechanisms are proposed for the reactions on discharge and charge. The different pathways for discharge and charge are consistent with the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

56
1,316
3
29

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,232 publications
(1,404 citation statements)
references
References 52 publications
56
1,316
3
29
Order By: Relevance
“…The onset of CO 2 evolution at 3.8 V is in accordance with the equilibrium potential of Reaction 1 ( E °=3.82 V vs. Li/Li + ) 4c, 6. Consistent with numerous studies, O 2 was not detected throughout charging 4c,4g,4h, 5b. H 2 and CO evolution is observed above 4.2 V during the anodic scan of the Li 2 CO 3 ‐packed electrodes, but no gas evolution is observed below 4.5 V from blank carbon black electrodes (Figure S3).…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The onset of CO 2 evolution at 3.8 V is in accordance with the equilibrium potential of Reaction 1 ( E °=3.82 V vs. Li/Li + ) 4c, 6. Consistent with numerous studies, O 2 was not detected throughout charging 4c,4g,4h, 5b. H 2 and CO evolution is observed above 4.2 V during the anodic scan of the Li 2 CO 3 ‐packed electrodes, but no gas evolution is observed below 4.5 V from blank carbon black electrodes (Figure S3).…”
supporting
confidence: 90%
“…While it is clear that Li 2 CO 3 decomposition evolves CO 2 , the fate of the third O atom in CO 3 2− has been an enduring open question since no O 2 evolves, although this would be expected from the formal oxidation reaction:3e, 4c,4f–4h,4j, 5b true20.166667emLi2CO340.166667emLi++40.166667emnormale-+20.166667emCO2+normalO24ptE=3.820.166667emnormalV4ptvs.4ptLi/Li+ …”
mentioning
confidence: 99%
“…The excellent cycling performance of the Fe@NCNT electrode indicates the stable electrochemical behavior with reduced polarization and high rever- sibility originated from the coupling of Fe and NCNTs at molecular level. It should be noted that the cycling performance of current Li-O2 batteries is largely harmed by the decomposition of the organic electrolyte during the electrochemical reaction [8,60]. With more stable electrolyte, the lifespan of the cells with Fe@NCNT electrode may be significantly extended for practical application.…”
Section: Resultsmentioning
confidence: 99%
“…(1) It has been shown that superoxide reacts irreversibly with most known electrolytes 10 and it is also probably involved in the corrosion of carbon electrodes. 11 Intensive research has been done on finding alternative electrolytes and electrode materials that are resistant towards degradation by superoxide.…”
mentioning
confidence: 99%